PENGARUH BRAND CREDIBILITY TERHADAP WORD OF MOUTH MELALUI CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA TOKO SARINANDE CILEGON - Candy Adeline; Rudy Pramono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
ABSTRACTThis research was conducted to determine the influence of Brand Credibilitytowards Word of Mouth through Customer Satisfaction and Customer Loyalty atSarinande Cilegon. This research held in Cilegon, involving 110 respondentswho had shopped at Sarinande Cilegon. Data collected by distributingquestionnaires containing 285 questions with Likert Scale of one to five based onnon-probability sampling method with convenience sampling technique. Datawas analyzed with Partial Least Sqaure (PLS) based Strutural EquationModelling (SEM) method. The result of this research state that customersatisfaction id proven to mediate the influence of brand credibility towards word of mouth, but not with customer loyalty. The positive influence was also provenon the influence of customer satisfaction and customer loyalty to word of mouth,and also had a positive influence on the effect of customer satisfaction oncustomer loyalty. Whereas it was not proven that brand credibility had a positiveinfluence towards customer loyalty